Pengaruh Viral Marketing dan Turbo Marketing Terhadap Keputusan Pembelian Produk Somethinc: (Studi Pada Konsumen di Kota Medan) - Lidia Katarina Sitanggang; Feronica Simanjorang; Onan Marakali Siregar (PT. Alahyan Publisher Sukabumi, 2025)
The development of digital marketing has transformed consumer behavior, including in purchasing decisions for skincare products. This study aims to analyze the effect of viral marketing and turbo marketing on the purchasing decisions of Somethinc products in Medan City. The research method used was associative quantitative with a sample of 97 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed with multiple linear regression. The results show that Viral Marketing has a positive and significant effect on Purchase Decisions with a t-value of 10.982 > 1.985 and a significance of 0.000. Turbo Marketing also has a positive and significant effect with a t-value of 3.480 > 1.985 and a significance of 0.000. Simultaneously, both variables have a significant effect with an F-value of 169.273 > 3.094. The Adjusted R Square value of 0.778 indicates that 77.8% of the variation in Purchase Decisions can be explained by these two variables, while the remaining 22.2% is influenced by other factors outside the model.